Emociones que experimentan las mujeres en torno a la violencia obstétrica (2024)
Obstetric Violence (OV) is defined as a practice carried out by health personnel in any of the hospital services, where the physical and psychological health of women during pregnancy, childbirth or the postpartum period is put at risk. The World Health Organization considers the condition of obstetric violence when some of the following scenarios described are experienced by the mother or the newborn: physical aggression and verbal or physical humiliation, medication or procedures without justification, activities where consent is not obtained of the mother and is not provided with the necessary information, hospital centers without conditions for service, nor adequate personnel and discrimination from a religious point of view, due to age, or underlying pathologies.